2021
DOI: 10.1111/mmi.14825
|View full text |Cite
|
Sign up to set email alerts
|

The novel repressor Rce2 competes with Ace3 to regulate cellulase gene expression in the filamentous fungus Trichoderma reesei

Abstract: Lignocellulosic biomass, which primarily consists of cellulose, hemicellulose, and lignin, is a renewable and abundant resource for the production of biofuels and chemicals (Peterson & Nevalainen, 2012;Ulaganathan et al., 2015). Cellulase can convert lignocellulosic biomass into fermentable sugars in an environmentally friendly manner, thus providing a promising approach for this process (Luo et al., 2020). The filamentous fungus Trichoderma reesei is a well-known industrial producer of cellulase and hemicellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Recently, the biological function of a novel repressor RCE2 was characterized to repress expression of a majority of cellulase genes, and transcription factors such as cre1 , xyr1 and ace3 . A binding competition between RCE2 and ACE3 was also observed, indicating a synergetic regulation among RCE2 and other transcription factors (Chen et al 2021c ).…”
Section: Cellulase Induction Is Regulated At the Transcription Levelmentioning
confidence: 99%
“…Recently, the biological function of a novel repressor RCE2 was characterized to repress expression of a majority of cellulase genes, and transcription factors such as cre1 , xyr1 and ace3 . A binding competition between RCE2 and ACE3 was also observed, indicating a synergetic regulation among RCE2 and other transcription factors (Chen et al 2021c ).…”
Section: Cellulase Induction Is Regulated At the Transcription Levelmentioning
confidence: 99%
“…In another study, Rce2, a protein recently identified by a pull-down and mass spectrometry analysis was found to have similar binding sites in the promoter regions of target genes as Ace3, and its overexpression led to reduced cellulase expression i.e. Rce2 acted antagonistic to Ace3 in T. reesei with regards to cellulase induction and led to repressed cellulase and hemicellulase expression [ 147 ].…”
Section: Recent Developments In Identification Of Other Transcription...mentioning
confidence: 99%
“…In addition, Cre1 represses the expression of the activators of cellulase expression, such as Xyr1 [13]. Also, Rce1 and Rce2 are cellulase-specific repressors that compete with Xyr1 and Ace3, respectively, for binding to the cel7a promoter [14,15]. Despite extensive studies, several TFs and different regulatory mechanisms that-in a coordinated way-regulate the expression of all the arsenal to degrade the plant cell wall are still unknown.…”
Section: Introductionmentioning
confidence: 99%